Penguatan Peran Ibu dalam Pencegahan Stunting melalui Edukasi dan Deteksi Pertumbuhan Balita - Nabilah Nurul Ilma; Hasri Yulianti; Nurlaelah Al-Tadom; Namsyah Baso; Hardian Bimanto (Rena Cipta Mandiri, 2025)
The role of mothers is very strategic in preventing stunting through fulfilling nutritional needs during pregnancy, providing exclusive breastfeeding, implementing balanced nutritional complementary feeding (MP-ASI), and regularly monitoring child growth and development. Mothers also play a role in maintaining environmental cleanliness, accessing basic health services (ANC, immunization, iron supplementation), and implementing responsive parenting practices. Objective: This Community Service Program aims to improve mother’s knowledge in preventing and managing stunting through nutrition education, growth and development monitoring. Methods: The methods used in this program included screening, lectures, and discussions, with sequential stages consisting of field observation and problem identification, proposing solutions, activity planning, implementation, and evaluation. Activities were carried out through interactive counseling sessions, demonstrations of growth monitoring, and screening or detection of child growth status. Results: The results showed a significant increase in mothers’ knowledge. The proportion of mothers with knowledge increased from 30% to 90% after receiving the educational intervention. Conclusion: The educational activities implemented were proven effective in strengthening mothers’ capacity in stunting prevention and have the potential to reduce stunting risk at the household and community levels. Structured and targeted education needs to be continuously enhanced as part of strategies to accelerate stunting prevention.